Profiles dinosaurs! - 20160731 frey50; Encyclopaedia Britannica, inc. (Chicago, Ill. : Encyclopaedia Britannica, 2003)
Watch a tyrannosaurus running, see how you measure up to him (would you reach his knee, his back, or his neck?), and explore the evolution of dinosaurs in an interactive timeline.
Microsoft Windows 98, 2000, Me, XP, NT (with Service Pack 5 or higher) ; Pentium 266 MHz, 350 MHz recommended ; 128 MB RAM, 256 MB recommended ; 60 MB free hard drive space ; CD-ROM drive ; 800 X 600 resolution, 16 bit color ; mouse or pointing device ; sound card and speakers recommended ; printer recommended ; Internet access recommended.
Macintosh OS 10.1 or higher ; iMac or G3 350 MHz or faster processor ; 128 MB RAM, 256 MB recommended ; 60 MB free hard drive space ; CD-ROM drive ; 800 X 600 resoulution, millions of colors ; mouse or pointing device ; sound card and speakers recommended ; printer recommended ; Internet access recommended.
Keywords: Dinosaurs